The mediating role of employee job performance in the impact of open book management dimensions on customer satisfaction - Alkhamis, Faisal Abdulkarim (Business: Theory and Practice, 2018)
This study aimed at investigating the impact of open book management (OBM) on customer satisfaction in the presence of employee job performance as a mediating variable. OBM was measured using employee empowerment, information sharing, employee training, and employee participation in organizational success. A sample consisted of 500 managers and employees from 10 industrial companies in Qassim region were participated in the study. Data were gathered using a questionnaire administered to participants. The final number of questionnaires received was 387 questionnaires with a response rate of 77.4 percent. The results showed positive as well as significant effects of employee training, empowerment and participation on employee job satisfaction and customer satisfaction. The results further pointed out that employee job performance mediated the effect of open book management dimensions on customer satisfaction. The originality of this study wells up from its contribution to literature as it underlined that employee training in the context of open book management should take the first priority, followed by employee empowerment as empowerment efforts do not bear its desired fruits in the absence of an employee who is able to properly implement what he or she empowered to do. It was recommended on the ground of these results to consider employee training, then employee empowerment in the context of OBM. An adoption of OBM is required to keep tabs on employee job performance in order to ensure an effective practice of OBM.